2015
DOI: 10.1016/j.nano.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Safe lipid nanocapsule-based gel technology to target lymph nodes and combat mediastinal metastases from an orthotopic non-small-cell lung cancer model in SCID-CB17 mice

Abstract: Lung cancer is one of the leading causes of mortality worldwide. A significant proportion of patients with this disease have lymph node metastasis. In this study, the authors investigated the use of lipid nanocapsules, loaded with the lipophilic pro-drug gemcitabine for targeting tumors in lymph nodes after subcutaneous injection. This delivery method was shown to be effective in controlling tumor progression and may be useful in future clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…1a). Thus, the physiochemical properties of these LNCs were similar for particles with and without DiD, as also reported by others [24]. The LNC particles were stable in PBS when stored at room temperature for more than 24 h (data not shown).…”
Section: Physiochemical Properties Of the Lncssupporting
confidence: 88%
“…1a). Thus, the physiochemical properties of these LNCs were similar for particles with and without DiD, as also reported by others [24]. The LNC particles were stable in PBS when stored at room temperature for more than 24 h (data not shown).…”
Section: Physiochemical Properties Of the Lncssupporting
confidence: 88%
“…Another study looked at lipid-based nanocapsules in a hydrogel for lymphatic targeting. Wauthoz et al used a lauroyl derivative of gemcitabine and administered the formulation subcutaneously or intravenously to target the lymphatic system, decrease the toxicity associated with gemcitabine therapy, and fight against mediastinal metastases in a mouse model with orthotopic non-small cell lung cancer in immunodeficient mice [155]. The biodistribution study indicates that the nanocapsules were targeted to the lymph nodes, caused no significant myelosuppression compared to normal saline, and significantly prolonged survival compared to standard therapy and control.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition to lymph-node targeting efficacy, SC administration was a promising alternative to conventional IV administration to avoid severe side effects due to too much systemic exposure to chemotherapeutics. Using gemcitabine-loaded LNCs, recent results have shown that SC administration reduced the myelosuppression that is observed after IV administration (22), at the same dose.…”
Section: Discussionmentioning
confidence: 99%